1980
DOI: 10.1111/j.1471-0528.1980.tb04540.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Foley's Catheter in Ripening the Unfavourable Cervix Prior to Induction of Labour

Abstract: Foley's catheter was used to ripen the cervix prior to induction of labour in 21 primigravidae and the results compared with those obtained using 5 mg of prostaglandin E, in vaginal gel in another group of 14 primigravidae. The improvement in cervical score and outcome of induction of labour was similar in both groups. There were no complications attributable to the use of these agents. Foley's catheter is easy to use, cheap and readily available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…The need for oxytocin augmentation was 39 (78%) in group 1 and 32 (68%) in group 2 in agreement with other studies [12][13][14]. Foley catheter is as effective as vaginal prostaglandin in enhancement of inducibility, with similar induction to delivery intervals and outcomes of labour.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The need for oxytocin augmentation was 39 (78%) in group 1 and 32 (68%) in group 2 in agreement with other studies [12][13][14]. Foley catheter is as effective as vaginal prostaglandin in enhancement of inducibility, with similar induction to delivery intervals and outcomes of labour.…”
Section: Discussionsupporting
confidence: 79%
“…Ezimokhai and Nwabinelli [12] found that ripening effect of a Foley catheter on the cervix in 21 primigravida to be similar to that of 5 mg of PGE2 in vaginal gel in 14 primigravida. No complication was attributable to the use of either method but the Foley catheter was considered advantageous in its ease of use, economical and ready availability.…”
Section: Discussionmentioning
confidence: 99%
“…Preinduction of cervical ripening with intravaginal or intracervical prostaglandins applied through a Foley catheter was described by Calder et al [3] and later by McKenzie et al [4]. Many retrospective comparisons between prostaglandin application and the intrauterine catheter for preinduction of cervical ripening showed a similar efficacy [5][6][7][8][9]. In a prospective randomized study, Onge and Connors [10] compared labor inductions with intracervical prostaglandin E 2 and the intrauterine balloon catheter, and found no significant difference in any of the parameters tested.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 What is yet to be determined is how long such a catheter can be safely placed in the cervical canal until the cervix becomes favourable. Equally important is the issue of cervical ripening before 37 completed weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study from our department reported the safe use of the catheter for cervical ripening in the presence of fetal demise. 8 The objective of this present work was to determine how long the extra-amniotic catheter balloon can remain when used for cervical ripening before its spontaneous expulsion or removal by traction.…”
Section: Introductionmentioning
confidence: 99%